Thermal error and energy-saving performance evaluation of the energy-saving machine tool using new structural materials - Makoto KATO; Daisuke KONO; Hayato YOSHIOKA; Naohiko SUGITA; Akihide HAMAGUCHI; Kazumasa KONO; Kazunori IIJIMA; Yasuhiro KAKINUMA (Nihon Kikai Gakkai ronbunshu, 2020)
New energy saving methods are required to address global climate change and resource depletion. New structural materials such as Carbon fiber reinforced plastic (CFRP) are used also in nowadays machine tools applications for energy efficiency improvement by weight reduction. This research group succeed in being the first to develop the energy-saving machine tool using new structural materials, mainly CFRP. Furthermore, CFRP is expected to enhance thermal characteristics, which contributes to reduction of warm up drive and implement of idle reduction. First of all, the thermal deformation of the energy-saving machine tool is investigated through single axis feed motion by measuring a test bar. It is obtained that the thermal error is obviously suppressed and shows unique behavior in comparison with a based conventional machine tool. Next, the energy-saving performance is evaluated through machining test. Warm up drive minimization method is proposed in order to realize high precision form accuracy. The warm up drive time is estimated based on an estimation model, and the energy efficiency of warm up drive is improved 57.0% in comparison with the base machine.